Behavioral Economic Approaches to Influencing Children's Dietary Decision Making at School. (March 2017) - Madden, Gregory J.; Price, Joseph; Sosa, Frank A.
The health benefits of consuming fruits and vegetables (FVs) are clear, but most children do not eat them regularly. At school, FVs are available, but children often refuse them or throw them away. This review article illustrates the evidence for and against behavioral–economic approaches to increasing FV consumption in schools. Simple but effective interventions include prompting children to take FVs and serving vegetables before other foods are available. Also effective is reducing their handling costs (e.g., serving sliced fruit) and opportunity costs (e.g., scheduling lunch after recess). Still larger improvements can be achieved by improving the taste of FVs, or by incentivizing consumption. Although controversial, even small incentives can produce immediate and lasting effects. Game-based virtual incentives can reduce the costs of incentive systems, while minimizing concerns that children are being bribed into healthy habit formation.